Changes in the blood redox balance during a simulated duathlon race and its relationship with athletic performance - Tsuzuki, T.; Tsukioka, K.; Naito, H. (Physiological Reports, 2019)
The duathlon is an endurance multisport event that consists of sequential running, cycling, and further running. Imbalance in the redox homeostasis is associated with fatigued status and underperformance in various sports; however, there are no corresponding reports regarding the duathlon. The purpose of this study was to examine the changes in the blood redox balance during a simulated duathlon race and to determine the relationship between performance and the redox balance. Eight male triathletes participated in a simulated race, consisting of a 5-km run, 30 km cycling, and a further 5-km run, with 5 min rest between two parts to collect the blood samples. The serum levels of reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP) were measured and BAP/d-ROMs ratio and oxidative stress index (OSI) were calculated. The d-ROMs levels after the first Run were significantly increased compared with the levels observed before the race. Moreover, BAP levels increased significantly over the race. The BAP/d-ROMs ratio also gradually increased through the race, while the OSI was gradually decreased. In addition, a significant relationship was observed only between d-ROMs levels after the first Run and the first Run performance. These results suggest that the redox balance shifts toward reduction (antioxidation) during the duathlon race and increased oxidant potential levels are negatively correlated with performance in the early stages of the race.